Smart Education in the Context of Puducherry India - Gauri Sharma; Bhumika Sharma; Ashish Laddha (Emerging Trends in Languages, 2025)
This paper explores the concept of smart education and presents its conceptual framework in the context of Puducherry. It aims to enhance the understanding of smart education by analysing its fundamental components, including educational challenges, technological innovations, management strategies, policy frameworks, historical evolution, and emerging trends. The adoption of smart education has accelerated significantly in recent years, particularly during the COVID-19 pandemic, when educational institutions worldwide transitioned from traditional classroom-based instruction to digital and online learning environments. This transformation compelled educators and learners to adopt technology-driven pedagogical methods that foster flexibility, accessibility, and collaboration in education. Government policies and strategic initiatives across the globe have further supported the development of smart education by encouraging the integration of advanced technologies within the learning ecosystem. In the context of Puducherry, this paper discusses the technological architecture, core functions, and key challenges associated with implementing a comprehensive smart education system. It also emphasizes the importance of teacher training, efficient management, and robust digital infrastructure to ensure the sustainability of smart education initiatives. By addressing both hard challenges—such as infrastructure limitations and digital gaps—and soft challenges—including motivation, policy alignment, and adaptability—this study provides valuable insights into strengthening the educational landscape of Puducherry. The paper concludes by underscoring the need for continuous innovation, inclusive policies, and stakeholder collaboration to achieve a sustainable, technology-driven educational transformation that aligns with future learning demands.
Keywords: Challenges; Policy; Puducherry; Smart education; technological framework